India and the illusion of economic growth - Mody, Ashoka (Henry Stewart Talks, 2024)
GDP growth, India, Growth rate, Quality of life, lived reality, Inequality, Mass education, Democracy, Hyper individualism, Dignified jobs, Involuntary leisure, Civic consciousness